Multigene phylogeny supports diversification of four-eyed fishes and one-sided livebearers (Cyprinodontiformes: Anablepidae) related to major South American geological events. - Pedro F Amorim; Wilson J E M Costa (PLoS ONE, 2018)
The high diversity of Neotropical fishes has been attributed to major South American palaeogeographic events, such as Andean uplift, rise of the Isthmus of Panama and marine transgressions. However, the unavailability of temporal information about evolution and diversification of some fish groups prevents the establishment of robust hypotheses about correlations between species diversification and proposed palaeogeographical events. One example is the Anablepidae, a family of teleost fishes found mostly in coastal habitats of Central and South America, but also in some inner river basins of South America. Historical aspects of the distribution patterns of the Anablepidae were never analysed and no accurate estimation of time of its origin and diversification is presently available. A multi-gene analysis was performed to estimate Anablepidae phylogenetic position, age and biogeography, comprising seven nuclear genes. The suborder Cyprinodontoidei was recovered in three major clades, one comprising all the Old World Cyprinodontoidei and two comprising New World lineages. Anablepidae was recovered as the sister group of the New World Poeciliidae, with the Amazonian genus Fluviphylax as their sister group. The ages found for the origin and diversification of Cyprinodontiformes were congruent with the pattern recorded for other vertebrate groups, with an origin anterior to the Cretaceous-Paleogene (K-Pg) transition and diversification during the Paleogene. The age estimated for the split between the Atlantic and Pacific lineages of Anableps was congruent with the rise of Panamanian Isthmus. The results suggest Miocene marine transgressions as determinant to the current distribution of Jenynsia.